Corticosterone as a Potential Confounding Factor in Delineating Mechanisms Underlying Ketamine’s Rapid Antidepressant Actions - Wegman-Points, Lauren; Pope, Brock; Zobel-Mask, Allison; Winter, Lori; Wauson, Eric; Duric, Vanja; Yuan, Li-Lian (Frontiers in Pharmacology, 2020)
Recent research into the rapid antidepressant effect of subanesthetic doses of ketamine have identified a series of relevant protein cascades activated within hours of administration. Prior to, or concurrent with, these activation cascades, ketamine treatment generates dissociative and psychotomimetic side effects along with an increase in circulating glucocorticoids. In rats, we observed an over 3-fold increase in corticosterone levels in both serum and brain tissue, within an hour of administration of low dose ketamine (10mg/kg), but not with (2R, 6R)-hydroxynorketamine (HNK) (10mg/kg), a ketamine metabolite shown to produce antidepressant-like action in rodents without inducing immediate side-effects. Hippocampal tissue from ketamine, but not HNK, injected animals displayed a significant increase in the expression of sgk1, a downstream effector of glucocorticoid receptor signaling. To examine the role conscious sensation of ketamine’s side effects plays in the release of corticosterone, we assessed serum corticosterone levels after ketamine administration while under isoflurane anesthesia. Under anesthesia, ketamine failed to increase circulating corticosterone levels relative to saline controls. Concurrent with its antidepressant effects, ketamine generates a release of glucocorticoids potentially linked to disturbing cognitive side effects and the activation of distinct molecular pathways which should be considered when attempting to delineate the molecular mechanisms of its antidepressant function.